2019
DOI: 10.3389/fphar.2019.01133
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of NaoShuanTong Capsule in the Treatment of Ischemic Stroke: A Meta-Analysis

Abstract: Background: Ischemic stroke (IS) is a leading cause of death and long-term disability worldwide. The NaoShuanTong capsule (NSTC), a traditional Chinese patent medicine, has been extensively used in the treatment of stroke in China. However, the clinical efficacy and safety of this treatment has not been statistically and systematically verified by any comprehensive pooled analysis. We therefore performed a meta-analysis to evaluate the efficacy and safety of NSTC in the treatment of IS.Methods: Randomized cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…As a result, previous meta-analyses have reported that the efficacy of blood-activating and stasis-dispelling herbs may be related to the severity of ischemic stroke. In addition, tPA, MTE plus tPA, MTE plus Stent Retrievers, blood-activating and stasisdispelling herbs plus XM was reported as only a modest but significant effect found on behavior in ischemic stroke patients (Peng et al, 2014;Punal-Rioboo et al, 2015;Kaesmacher et al, 2019;Shang et al, 2019;Zhang et al, 2019). In our study, Alpha1 was more effective for neurological improvement rate compared with placebo.…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…As a result, previous meta-analyses have reported that the efficacy of blood-activating and stasis-dispelling herbs may be related to the severity of ischemic stroke. In addition, tPA, MTE plus tPA, MTE plus Stent Retrievers, blood-activating and stasisdispelling herbs plus XM was reported as only a modest but significant effect found on behavior in ischemic stroke patients (Peng et al, 2014;Punal-Rioboo et al, 2015;Kaesmacher et al, 2019;Shang et al, 2019;Zhang et al, 2019). In our study, Alpha1 was more effective for neurological improvement rate compared with placebo.…”
Section: Discussionmentioning
confidence: 44%
“…In all, 207 studies were excluded due to the following reasons: samples overlap with other studies (n = 80), no necessary sample data (n = 45), other outcomes (n = 27), other stroke (n = 20), other language (n = 17), no placebo group (n = 11), mild cognitive impairment (n = 7), (Figure 1). Thus, 43 studies were included in the umbrella review: Pan et al, 2020;Pan et al, 2020); Liu et al, 2021); (Liu et al, 2011);Blann et al, 2015); (Blann et al, 2015); Emberson et al, 2014) (Emberson et al, 2014); Peng et al, 2014); (Peng et al, 2014); Zhang et al, 2019); Shang et al, 2019); Puñal-Riobóo et al, 2015;Yuan et al, 2008;(Fu et al, 2013), Fan et al, 2014), Lin et al, 2014; Xu et al, 2015); Cao and Li, (2015); Marmagkiolis et al, 2015); Zheng et al, 2017), Li et al, 2017), Zhang et al, 2017), Chong et al, 2020); (Zhao et al, 2021), Li et al (2020); (Li et al, 2020), Gao et al, 2021); Huang et al, 2020); (Huang and Xiao, 2021), Liu et al, 2022), Feng et al, 2021, Lee et al (2010); Zhou et al, 2022); Hu et al, 2021); Lee, 2015, Liu et al, 2021); (Liu et al, 2021), Xin et al, 2020);…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also extensively used for increasing blood circulation, eliminating blood stasis, and promoting nerve function recovery ( Liu et al, 2014 ). Moreover, a meta-analysis showed that NST has the effect of increasing blood adiponectin, decreasing neurological deficits, and reducing the area of atherosclerotic plaque ( Zhang et al, 2019 ). Since it has been widely used to treat ischemic stroke, Liu and Huang demonstrated that NST + WM is better than WM in recurrent stroke, and the results are significantly different ( Liu and Li, 2012 ; Huang et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most ethnic drugs for treatment of ischemic stroke have the function of activating blood circulation to remove blood stasis or clear collaterals. NaoShuanTong capsule (Zhang H. et al, 2019), ShenQi Fuzheng injection (Cai et al, 2016), ShengMai injection (Yang et al, 2016), and PeiYuan TongNao capsule have been reported to significantly improve the symptoms of ischemic stroke with few adverse events. In recent years, some antiapoptotic protective effects of cerebral ischemia have also been reported, such as XueShuanTong injection (Li et al, 2009) and QianCao NaoMaiTong mixture (Lu et al, 2016).…”
Section: Authorized Products For Stroke Improvement By Regulating Mitmentioning
confidence: 99%